ANALISIS PERAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS KARYAWAN DI DEPARTEMEN PROCUREMENT WAREHOUSE PT. SEMEN BATURAJA - Rebeka Simanjuntak, Egrifa Ovelina; Safaruddin, Safaruddin; Furwanto, Edi (JIM : Journal Of International Management, 2022)
At first human resources were nothing but production factors, nowadays human resources are an important and very decisive factor in the implementation of the organization's vision and mission. In addition to the capital factor, human resources (HR) is one of the most important issues in a company/organization. Therefore, human resources must be managed properly to increase the effectiveness and efficiency of an organization. Human Resources (HR) is one of the most important factors and cannot be separated from both organizations and companies. HR is also the key to the development of a company. Basically HR in the form of people employed by an organization as actors, thinkers, and planners to achieve organizational goals. Quality is a very difficult concept to understand and agree on. The word quality currently has many different interpretations, cannot be defined individually and is very dependent on the context. In other words, the quality of an employee's work is a minimum standard that must be met so that the employee can carry out his work well.